The Diversity of Mollusks (Bivalve and Gastropod) in the Intertidal Zone of Mutun Coastal, Padang Cermin, Lampung - Restu Ayu Ningtias; Raden Teti Rostikawati; Meilisha Putri Pertiwi; Enriani Manullang; Dhia Nida Fauzia (Journal Of Biology Education Research (JBER), 2024)
Mutun Coastal has a diversity of biota species. Biota that are commonly found include the mollusk phylum (Bivalve and Gastropod classes). The purpose of this study was to determine the diversity of mollusks (Bivalves and Gastropods) on Mutun Coastal Lampung. This research was conducted on February 5-7, 2021. The method of data retrieval at both stations used the belt transect method by purposive sampling. Station I is substrated fine sand, while station II is substrated by coarse sand. Based on the research conducted, 26 individuals were found consisting of 7 families, namely 6 families of the Gastropod class (Trochidae, Strombidae, Cerithiidae, Muricidae, Potamididae and Pisaniidae) and 1 family of the Bivalve class, namely the family Mactridae. The value (H') at station I is 1.44.  At station II it has an H' value of 0.86. The value of H' at station I belongs to the medium category. The H' value at station II belongs to the low category. The value of E at station I is 0.72. While at station II it has a value of 0.1. The evenness value at station I belongs to the high category. The value (E) at station II of the evenness index belongs to the low category. The value (D) at station I is 0.57. While at station II it has a value of 0.35. The value of D at station I belongs to the medium category. The value of D at station II belongs to the medium category. Based on data analysis, Mutun Coastal has suitable habitat for mollusk and it is also supported by abiotic parameter conditions.